2021
DOI: 10.5811/westjem.2021.1.49279
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Access During COVID-19: Disparities in Utilization by Race/Ethnicity, Insurance, and Income

Abstract: Introduction In March 2020, shelter-in-place orders were enacted to attenuate the spread of coronavirus 2019 (COVID-19). Emergency departments (EDs) experienced unexpected and dramatic decreases in patient volume, raising concerns about exacerbating health disparities. Methods We queried our electronic health record to describe the overall change in visits to a two-ED healthcare system in Northern California from March–June 2020 compared to 2019. We compared weekly abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…The large increase in the incidence of CA and ACS events in the population of age 16-39 parallel to the vaccination rollout and its association with the vaccination rates could be consistent with the known causal relationship between the mRNA vaccines and incidents of myocarditis in young people 14,17,19,56 , as well as the fact that myocarditis is often misdiagnosed as ACS [28][29][30] , and that asymptomatic myocarditis is a frequent cause for unexplained sudden death among young adults from CA 26,[31][32][33] . This is further supported by more anecdotal reports describing sudden cardiac death following COVID-19 vaccination 16,57 .…”
Section: Discussionsupporting
confidence: 57%
“…The large increase in the incidence of CA and ACS events in the population of age 16-39 parallel to the vaccination rollout and its association with the vaccination rates could be consistent with the known causal relationship between the mRNA vaccines and incidents of myocarditis in young people 14,17,19,56 , as well as the fact that myocarditis is often misdiagnosed as ACS [28][29][30] , and that asymptomatic myocarditis is a frequent cause for unexplained sudden death among young adults from CA 26,[31][32][33] . This is further supported by more anecdotal reports describing sudden cardiac death following COVID-19 vaccination 16,57 .…”
Section: Discussionsupporting
confidence: 57%
“…Of note, however, such racial and insurance disparities in the acuity levels of imaging findings did not increase in 2020 compared with pre-pandemic levels. In contrast other studies have shown an exacerbation in health disparities and their underlying social determinants of heath during the pandemic [ 36 , 37 ]. Our analysis only included examinations during the first six months of the COVID-19 pandemic and only focused on acuity of brain MRI examinations.…”
Section: Discussionmentioning
confidence: 83%
“…Some papers have included data on ESI patterns of ED visits during this period in the tables or appendix, but they have mixed COVID-19 and non-COVID-19 patients.Those have not reported the trends in patient characteristics that we observed in this study. [17][18][19] The number of visits to the ED decreased worldwide during pandemic beginning, and our ED did not deviate from the rule. 20 This confirms our hypothesis that, in our ED, the number of visits decreased during the COVID-19 first wave and the non-COVID-19 patient visits were more urgent, based on the ESI triage tool.…”
Section: Discussionmentioning
confidence: 59%